2021
DOI: 10.1177/23259671211064626
|View full text |Cite
|
Sign up to set email alerts
|

The Statistical Fragility of Single-Bundle vs Double-Bundle Autografts for ACL Reconstruction: A Systematic Review of Comparative Studies

Abstract: Background: The statistical significance of a given study outcome can be liable to small changes in findings. P values are common, but imperfect statistical methods to convey significance, and inclusion of the fragility index (FI) and fragility quotient (FQ) may provide a clearer perception of statistical strength. Purpose/Hypothesis: The purpose was to examine the statistical stability of studies comparing primary single-bundle to double-bundle anterior cruciate ligament reconstruction (ACLR) utilizing autogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 49 publications
4
11
0
Order By: Relevance
“…For the outcomes included in this analysis, the median FI was 2.5 (IQR 2-4), the mean FI was 2.9 (±1.58), the median FQ was 0.032 (IQR 0.012-0.069), and the mean FQ was 0.049 (±0.062). These values are consistent with the current orthopaedic literature reporting an average median FI of 3.81 10 14 , 17 , 18 , 21 , 23 , 29 31 , 36 , 38 , 42 , 47 53 , 55 …”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…For the outcomes included in this analysis, the median FI was 2.5 (IQR 2-4), the mean FI was 2.9 (±1.58), the median FQ was 0.032 (IQR 0.012-0.069), and the mean FQ was 0.049 (±0.062). These values are consistent with the current orthopaedic literature reporting an average median FI of 3.81 10 14 , 17 , 18 , 21 , 23 , 29 31 , 36 , 38 , 42 , 47 53 , 55 …”
Section: Discussionsupporting
confidence: 92%
“…These values are consistent with the current orthopaedic literature reporting an average median FI of 3.81 1014,17,18,21,23,29 31,36,38,42,47 53,55 57 and FQ of 0.048. 1012,18,21,…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Twelve reviews reported FI values stratified by primary vs secondary outcome type. Two studies reported no statistically significant difference between primary and secondary outcome FI values [18, 19], while one study did report a significant difference [14]. Nine reviews investigated the relationship between FI values and journal impact factor.…”
Section: Resultsmentioning
confidence: 99%